2009
DOI: 10.1056/nejmoa0806326
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Case of Deer Tick Virus Encephalitis

Abstract: SUMMARY Deer tick virus is related to Powassan virus, a tickborne encephalitis virus. A 62-year-old man presented with a meningoencephalitis syndrome and eventually died. Analyses of tissue samples obtained during surgery and at autopsy revealed a widespread necrotizing meningoencephalitis. Nucleic acid was extracted from formalin-fixed tissue, and the presence of deer tick virus was verified on a flavivirus-specific polymerase-chain-reaction (PCR) assay, followed by sequence confirmation. Immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 24 publications
2
84
0
2
Order By: Relevance
“…Recent increases in the deer populations in the northeastern and upper midwestern United States and associated increases in the range and abundance of deer ticks, coupled with the increasing incidence of human infection with deer tick-borne agents suggest that the current burden of tick-borne flaviviruses may be due mainly to DTV and not POWV. Furthermore, because several recent reports have documented severe cases of infection by DTV/POWV, 3,20,21 our results suggest that tick-borne flaviviruses should be considered in the differential diagnosis for persons who might have a history of tick exposure and neurologic symptoms.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Recent increases in the deer populations in the northeastern and upper midwestern United States and associated increases in the range and abundance of deer ticks, coupled with the increasing incidence of human infection with deer tick-borne agents suggest that the current burden of tick-borne flaviviruses may be due mainly to DTV and not POWV. Furthermore, because several recent reports have documented severe cases of infection by DTV/POWV, 3,20,21 our results suggest that tick-borne flaviviruses should be considered in the differential diagnosis for persons who might have a history of tick exposure and neurologic symptoms.…”
Section: Discussionmentioning
confidence: 65%
“…1 A subtype of POWV, frequently termed deer tick virus (DTV), was first identified in 1995 2 and has subsequently been recognized as a human pathogen. 3 Because it is associated with the aggressively human-biting blacklegged or deer ticks (Ixodes scapularis), 4,5 this virus has been considered to pose a more significant threat to public health than the prototype virus, POWV, that is associated mainly with the relatively host-specific ticks Ixodes cookei and I. marxi. 6,7 Recent studies have suggested that the incidence of human POWV infection is increasing in the United States, 8 raising the possibility that POWV, like other members of the deer tick-associated guild of emerging zoonoses (Lyme disease, human babesiosis, and human granulocytic anaplasmosis), constitutes a mounting threat in regions where it is enzootic and where I. scapularis ticks are abundant.…”
Section: Introductionmentioning
confidence: 99%
“…1 Both lineages have been isolated from ticks, 11,12 and both have been isolated or detected in tissues from fatal human cases of encephalitis. 2,13 Despite the absence of reported human POWV cases in Connecticut, human disease has been recognized in the adjoining state of New York, and the virus has been isolated from ticks in Connecticut. 11,12 In this study, we report 30 additional isolations of POWV from I. scapularis from two distinct geographical areas in Connecticut, an improved in vitro method for the isolation of this virus from ticks, the stability of two distinct genetic strains of POWV from two geographically separated populations over multiple years, and the focal nature of POWV.…”
Section: Introductionmentioning
confidence: 99%
“…12 The lesion found in our patient MRI (Figure) does not seem to be relevant to this clinical finding. We could hypothesize that a mesencephalic lesion may have created that clinical picture, since both reflexive and intentional saccades were affected, with a particular involvement of the superior colliculus, but this may not explain the initial smooth pursuit impairment, more involved at the pontine level among the brainstem, which consequently necessitate multifocal brainstem lesions.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, an autopsy done previously on a patient with PE but without SO showed prominent involvement of large neurons in the brainstem, cerebellum, basal ganglia, thalamus, and spinal cord, but not in the cortex. 12 To our knowledge, this is the second reported case of SO in PE.…”
Section: Discussionmentioning
confidence: 64%